2016
DOI: 10.1002/ijc.30076
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and significance of tumor‐associated neutrophils in patients with colorectal cancer

Abstract: Inflammatory cells are an essential component of the tumor microenvironment. Neutrophils have emerged as important players in the orchestration and effector phase of innate and adaptive immunity. The significance of tumor-associated neutrophils (TAN) in colorectal cancer (CRC) has been the subject of conflicting reports and the present study was designed to set up a reliable methodology to assess TAN infiltration in CRC and to evaluate their clinical significance. CD66b and myeloperoxidase (MPO) were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 52 publications
(160 reference statements)
3
131
1
Order By: Relevance
“…Furthermore, recent evidence shows that TANs are endowed with considerable plasticity basing on environmental cues. In CRC, the presence and significance of TANs have been the subjects of conflicting reports 20, 22, 24. In this present study, we set out to rigorously evaluate the prognostic significance of TANs in CRC.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, recent evidence shows that TANs are endowed with considerable plasticity basing on environmental cues. In CRC, the presence and significance of TANs have been the subjects of conflicting reports 20, 22, 24. In this present study, we set out to rigorously evaluate the prognostic significance of TANs in CRC.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, low TAN levels identified a subgroup of muscle invasive bladder cancer (MIBC) patients who appeared to benefit from adjuvant chemotherapy 16. In CRC patients, Galdiero et al22 revealed that a higher TAN density was associated with a better response to 5‐FU‐based chemotherapy. And this also indicates that neutrophils show different functions under different tumor microenvironments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations